Didactical Situations and Learning Obstacles in Geometric Sequences among High School Students - Wulan Putri Utami; Mohamad Gilar Jatisunda; Davron Aslonqulovich Juraev; Mohamed Nor Azhari Azman (AlphaMath : Journal of Mathematics Education, 2026)
This study examines didactic situations by integrating an analysis of students’ learning obstacles in mathematics education, particularly on geometric sequences, which remains a persistent source of conceptual difficulty for students. The purpose of this study is to analyze didactic situations based on the Theory of Didactical Situations and to identify the types and emergence of students’ learning obstacles within each stage of the learning process. A descriptive qualitative approach was employed involving 36 eleventh-grade students divided into six groups. Data were collected through classroom observations, conceptual tests, and semi-structured interviews and analyzed using data reduction, data display, and conclusion-drawing techniques. The findings show that all stages of the Theory of Didactical Situations—action, formulation, validation, and institutionalization—were implemented systematically, each characterized by distinct patterns of students’ activities and interactions with the milieu. Nevertheless, students still encountered ontogenic obstacles during the action phase related to readiness and confidence, epistemological obstacles during the formulation phase in the form of misconceptions and difficulties in identifying multiplicative patterns, and didactical obstacles during the validation phase, characterized by limited participation and weak argumentative skills in discussions. These results indicate that learning obstacles are closely associated with the characteristics of each stage of the didactical situation. This study contributes an integrated analysis linking didactic situations with the emergence of students’ learning obstacles at each stage of the TDS through interactions with the milieu. The findings emphasize the importance of adaptive, student-centered instruction to strengthen conceptual understanding and reduce obstacles to learning in mathematics.